2008
DOI: 10.1590/s0100-40422008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Constituintes químicos e atividade antiedematogênica de Peltodon radicans (Lamiaceae)

Abstract: ArtigoDedicamos este trabalho à Helena Ferraz, que nasceu e cresceu, e que me viu também nascer e crescer, em um daqueles muitos rincões mineiros encostados na Serra da Mantiqueira. Mantiqueira -do tupi "Amantikir" -a montanha que chora, agora chora e choramos ainda mais, por você, Helena. *e-mail: aalcantara@zeus.qui.ufmg.br Recebido em 4/6/07; aceito em 11/10/07; publicado na web em 10/3/08 CHEMICAL CONSTITUENTS AND ANTIEDEMATOGENIC ACTIVITY OF Peltodon radicans (Lamiaceae). Most of the snakebite incidents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
4
11
0
1
Order By: Relevance
“…The 13 C NMR data of 10 are similar to those of 9, except for the signals attributed to the alkenylic carbon atoms, which were only recorded two signals at δ C 140.8 and 121.7. These 13 C NMR data are in agreement with the corresponding data described for sitosterol (Costa et al, 2008). , 3058, 2946, 2918, 2852, 1638, 1464, 1387, 1378, 1189, 1096, 1036, 992, 822 , 3078, 3058, 2946, 2918, 2852, 1646, 1464, 1387, 1378, 1189, 1096, 1036, 992, 880, 822; 1 H NMR (400 MHz, CDCl 3 ) δ H 4.67 (s, H-29a), 4.56 (s, H-29b); 13 , 2848, 1736, 1473, 1461, 1376, 1217, 736, 718; 1 H NMR (400 MHz, CDCl 3 ) δ H 5.46 (m, H-7), 4.57 (dd, J = 10.9 and 4.5 Hz, H-3), 2.10 (s, CO 2 Me); 13 …”
Section: Evaluation Of the Bactericidal And Trypanocidal Activities Osupporting
confidence: 90%
See 2 more Smart Citations
“…The 13 C NMR data of 10 are similar to those of 9, except for the signals attributed to the alkenylic carbon atoms, which were only recorded two signals at δ C 140.8 and 121.7. These 13 C NMR data are in agreement with the corresponding data described for sitosterol (Costa et al, 2008). , 3058, 2946, 2918, 2852, 1638, 1464, 1387, 1378, 1189, 1096, 1036, 992, 822 , 3078, 3058, 2946, 2918, 2852, 1646, 1464, 1387, 1378, 1189, 1096, 1036, 992, 880, 822; 1 H NMR (400 MHz, CDCl 3 ) δ H 4.67 (s, H-29a), 4.56 (s, H-29b); 13 , 2848, 1736, 1473, 1461, 1376, 1217, 736, 718; 1 H NMR (400 MHz, CDCl 3 ) δ H 5.46 (m, H-7), 4.57 (dd, J = 10.9 and 4.5 Hz, H-3), 2.10 (s, CO 2 Me); 13 …”
Section: Evaluation Of the Bactericidal And Trypanocidal Activities Osupporting
confidence: 90%
“…The 13 C NMR spectrum showed signals at δ C 139.6 and 124.4, which are characteristic of the ursan skeleton, and signals at δ C 150.9 (non-hydrogenated carbon) and 109.3 (methylene carbon), which are characteristic of triterpenes with lupan skeleton. The 13 C NMR data of the mixture of 5 and 6 are in agreement with the corresponding data described for α-amyrin and lupeol (Costa et al, 2008), respectively.…”
Section: Evaluation Of the Bactericidal And Trypanocidal Activities Osupporting
confidence: 87%
See 1 more Smart Citation
“…In the case of P. megalophyllum, however, inhibition reached only 35.62 ± 1.9% in the first hour, while that of A. fragrans achieved only 21 ± 2.1%. Da Costa et al (2008) demonstrated that the leaves, bark, and roots of P. radicans, a plant used in the Amazon region for the treatment of snakebite, inhibited significantly the edematogenic activity of the venom of B. atrox.…”
Section: Inhibition Of Edematogenic Activitymentioning
confidence: 99%
“…In the Amazon region, for example, indigenous peoples use macerated leaves of Pentaclethra macroloba as an ointment for topical application on the site of bite (Da Silva et al, 2005). Concerning B. atrox, it has been reported that extracts from Marsypianthes chamaedrys reduced venom induced leukocyte migration (Magalhães et al, 2011), flowers extracts of Peltodon radicans inhibited the venom induced edema (Da Costa et al, 2008) and Humirianthera ampla extracts reduced 75% of the myotoxic effect of the venom (Strauch et al, 2013). However, the majority of plant species used in Amazonian folk medicine remains without scientific validation.…”
Section: Introductionmentioning
confidence: 99%